Peradaban Islam Pertumbuhan Awal Hingga Masa Kejayaan (Abad 1/7-13) - Anita Purnama Sari R; Mawaddatun Nikmah Harahap; Mhd Yanzhuri; Putri Wahyuni (Departement of Mathematics Education, 2023)
The purpose of this study was to find out the early growth of Islamic civilization to its heyday. The method in this study used the method (library research) by collecting a number of literaturer relating to the problem and research objectives. Data collection with the results of previous research which supports the data in this study. Islamic economics is part of a complete system of life based on the Koran, as-sunnah, lijma and qiyas. In Islam it is stated that the available resources are sufficient, therefore with their skills humans are required to prosper the world which is also a worship to their Lord. Economic development during the Umayyad dynasty had begun to increase compared to the previous period. Economic improvement, which in turn will bring prosperity to this dynasty, is basically inseparable from the policies implemented by the caliphs, in addition to the participation and support of the community for these policies. In Islam, the notion of science has several opinions of scholars. However, this difference has one thing in common, namely science is a way of understanding what something is to be understood. Then, something can be categorized as science if it is a device that can bring human life to a relatively easier and dignified direction for religious knowledge, is able to bring its owner to a more positive path, loves all creatures, the environment, and ultimately gets closer to God. creator. Advances in technology have provided facilities and welfare for mankind. There are three developments in Islam in the field of art, namely building art and architecture, in the form of mosque buildings and city buildings. Language Arts and literature, namely in the form of, the development of poetry, the development of prose. And the last is music.